Electron cyclotron harmonic waves in Jovian magnetosphere as seen by Juno - Joseph, J.; Jaynes, A. N.; Kurth, W. S.; Menietti, J. D.; Connerney, J. E. P.; Bolton, S. J. (Frontiers in Astronomy and Space Sciences, 2023)
Electron cyclotron harmonic (ECH) waves along with whistler mode waves are suggested to be responsible for causing the persistent diffuse aurora in Jupiter. In this work, for the first time we systematically analyze the ECH waves in the Jovian inner magnetosphere, which was surveyed by Juno during the later orbits (>25). We find that in the Jovian inner magnetosphere, ECH waves occur in two specific regionsone equatorial and the other off-equatorial, just outside the Io torus. Equatorial ECH waves have higher intensity compared to their off-equatorial counterpart. We also notice an overlap between the region of mid-latitude hot injections and the region of off-equatorial ECH wave occurrence. Finally, we show an event to describe the complex nature of ECH wave growth/damping varying with particle density structures of the injection region at mid-latitude.